Learning DevOps : the complete guide to accelerate collaboration with Jenkins, Kubernetes, Terraform and Azure DevOps - Krief, Mikael (Packt Publishing, 2019)
DevOps enhances the collaboration between the development and the operations teams within an organization. This book will give you a solid foundation of the best practices in DevOps - from implementing Infrastructure as Code, to building efficient CI/CD pipelines with Azure DevOps, to containerizing your apps with Docker and Kubernetes.